Changes in Intestinal Flora Structure and Metabolites Are Associated With Myocardial Fibrosis in Patients With Persistent Atrial Fibrillation - Liu, Langsha; Su, Juan; Li, Rui; Luo, Fanyan (Frontiers in Nutrition, 2021)
Background: The occurrence of atrial fibrillation is often accompanied by myocardial fibrosis. An increasing number of studies have shown that the intestinal flora is involved in the occurrence and development of a variety of cardiovascular diseases. This study explores the relationship between changes in the structure and function of the intestinal flora and the progression of myocardial fibrosis in patients with persistent atrial fibrillation. Methods: Serum and stool samples were collected from 10 healthy people and 10 patients with persistent atrial fibrillation (PeAF), and statistical analyses were performed on the subjects' clinical baseline conditions. ELISA was used to detect the levels of CTX-I, PICP, PIIINP, FGF-23 and TGF-β1 in serum. Through 16S rRNA sequencing technology, the structural composition of the intestinal flora was detected and analyzed. In addition, metabolomics data were analyzed to determine the differences in the metabolites produced by the intestinal flora of the subjects. Results: By comparing the baseline data of the subjects, it was found that compared with those of the control group, the levels of CRE and SUA in the serum of PeAF patients were significantly increased. In addition, we found that the levels of CTX-I, PICP, PIIINP and TGF-β1 in the serum of PeAF patients were significantly higher than those of the control group subjects. Although the control group and the PeAF group exhibited no significant differences in the α diversity index, there were significant differences in the β diversity indexes (Bray-Curtis, weighted UniFrac and Anosim). At the phylum, family and species levels, the community structure and composition of the intestinal flora of the control group and those of the PeAF group showed significant differences. In addition, the compositions of the intestinal metabolites in the two different groups of people were significantly different and were significantly correlated with PIIINP and certain communities in the intestinal flora. Conclusion: PeAF patients may have a higher risk of myocardial fibrosis, and changes in the structure and composition of their intestinal flora may lead to differences in intestinal metabolites. In addition, the intestinal flora may participate in the process of myocardial fibrosis in PeAF patients through metabolic pathways.